How Can SMEs Use Crowdfunding Platforms to Internationalize? The Role of Equity and Reward Crowdfunding - Troise, Ciro; Battisti, Enrico; Christofi, Michael; van Vulpen, Nina Jorien; Tarba, Shlomo (My University, 2023)
Despite the exponential growth of crowdfunding in recent years, research on the role it plays in business internationalization is still embryonal. Building on the Resource Based View (RBV) and Knowledge Based View (KBV), this study explores how SMEs can use equity crowdfunding (ECF) and reward crowdfunding (RCF) to internationalize and the related potential limitations. Using an inductive qualitative research design, based on multiple case studies of Italian SMEs, our study showed that ECF and RCF models help SMEs in acquiring the financial resources needed to internationalize and, at the same time, offer significant added value to their internationalization. Our findings support the idea that ECF and RCF play a key role in helping companies to overcome their resource limitations in regard to internationalization, not only in terms of the provision of financial resources but, above all, by compensating for any lack of knowledge on aspects relevant to the internationalization process. Furthermore, our results show the limitations of SMEs use of crowdfunding in order to internationalize (i.e., a lack of ad hoc e-commerce policies in relation to equity crowdfunding and to the regulation of the pre-ordering mechanism in the reward model). This paper concludes by discussing the theoretical and managerial contributions to the international business domain, and highlighting fruitful avenues for future studies.
Keywords: E-commerce policy; Equity crowdfunding; Financial resources; International business; Internationalization; Reward crowdfunding; SMEs